The Influence of Profitability and Tax Planning on Earnings Management with Company Size as a Moderating Variable - Matalauni, Yelis G; Tuli, Hartati; Wuryandini, Ayu Rakhma (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
This research aims to determine the effect of profitability on earnings management with company size as a moderating variable in cigarette sub-sector companies listed on the Indonesia Stock Exchange for the 2012-2021 period. The research object is a cigarette sub-sector company listed on the Indonesian Stock Exchange. Purposive sampling was used in sampling so that the remaining 3 company samples remained for the 10 year observation period. This research uses secondary data obtained from www.idx.co.id, www.gudanggaramtbk.com, www.sampoerna.com, and www.wismilak.com. Data analysis uses classical assumption tests, multiple linear regression analysis, hypothesis testing and Moderated Regression Analysis tests. The results of the study partially show that profitability and tax planning have no effect on earnings management. Simultaneously, profitability and tax planning have no effect on earnings management. Based on the results of the MRA interaction test, company size can moderate the effect of profitability on earnings management. However, company size cannot moderate the influence of tax planning on earnings management